Perceiving Duolingo beyond the classroom: insights from non-English major students in higher education - Suherman, La Ode Achmad; Hamka, Nurhadi; Akfan, Sofyan Sukwara (Universitas Mulawarman, 2024)
This study investigates how Duolingo can serve as a supplementary tool for English learning among non-English major students at Universitas Muhammadiyah Buton, focusing on students in the Faculty of Economics. The research aims to understand students’ perceptions of Duolingo’s effectiveness and the challenges they face when using the app beyond the classroom. A mixed-methods approach was employed, combining quantitative and qualitative data gathered from 120 first-year students over a six-week period. Quantitative data, collected through surveys, measured students’ usage patterns, motivation, and engagement levels, while qualitative data from open-ended responses provided insights into specific challenges and motivations related to Duolingo’s gamified features, such as XP, leaderboards, and levels. The findings indicate that Duolingo’s gamification elements contributed to increased motivation and engagement, particularly among students balancing academic and personal commitments. However, students faced challenges, including limited internet access, time constraints, and difficulty with advanced vocabulary and grammar. This study concludes that Duolingo is an effective supplementary tool for enhancing language learning outside the classroom, though additional support may be required to address connectivity issues and advanced language content.